The Baby-sitters remember - Martin, Ann M., 1955- (New York : Scholastic, 1994)
When the SMS teachers assign summer homework, "What I did this summer," the Baby-sitters start remembering when they were little, the sad times, happy times, and funny times.
"An Apple paperback.".
4.1
3-6
Keywords: Babysitters -- Fiction; Schools -- Fiction; Summer -- Fiction; Babysitters -- Fiction; School stories; Summer -- Fiction